The Influence of Compensation and Employment Status on Employee Performance with Work Motivation as a Mediating Variable - Elma Hariani; Lutfi (UNUSA Press, 2023)
This study examines the effect of compensation and employment status on employee performance with work motivation as a mediating variable. Research involved 64 employees of DHL Express Indonesia-Surabaya Branch. Data collection used a questionnaire consisting of 37 questions which designed based on previously research and tested for the validity and reliability. The data analysis technique in this study used Partial Least Squares (PLS). The results showed that compensation had an effect on employee performance but not significantly. Employment status had a direct and significant positive effect on employee performance. Compensation had a direct and significant positive effect on work motivation. Work motivation mediates the relationship between compentation on employee performance.